Jekaterinai Ripai veltīto apsveikumu kolekcija - Kuzņecova, Kristīne (My University, 2018)
Raksts par vēsturnieci, bijušo Latvijas Valsts Universitātes Vēstures un filoloģijas fakultātes dekāni (1961-1963) un Studentu zinātniskās biedrības sekcijas zinātnisko vadītāju docenti Jekaterinu Ripu (1902-1993) un viņai veltīto vēstuļu un apsveikumu kolekciju, kas glabājas Latvijas Universitātes Muzeja Vēstures kolekcijā.

An article about the historian, former dean of the Faculty of History and Philology of the Latvijas Valsts Universitāte (1961-1963) and scientific supervisor of the section of the Student Scientific Society Jekaterina Ripa (1902-1993), and the collection of letters and congratulations dedicated to her, that is stored in the History Collection of the Museum of the University of Latvia.
Collection of greeting cards dedicated to Jekaterina Ripa
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Jekaterina Ripa; Vēstures un filoloģijas fakultāte; Faculty of History and Philology; Studentu zinātniskā biedrība; Student scientific society; apsveikumi; greetings; Ilgvars Butulis